Conceptual modeling : 37th International Conference, ER 2018, Xi'an, China, October 22-25, 2018, Proceedings /: 37th International Conference, ER 2018, Xi'an, China, October 22-25, 2018, Proceedings. (2018) - Unknown
No abstract available